A rare case of near-haploid acute lymphoblastic leukemia. (2019) - Gonzalez-Marques, William; Zaslav, Ann-Leslie; Balakrishnan, Dhana; Hogan, Laura; Ma, Yupo; Tully, Daniel; Fernicola, Paula; Ponce, Roxana; Lee, Htien; Mercado, Theresa; Ahmed, Tahmeena
Abstract: Near-haploid acute lymphoblastic leukemia is seen in <1% of cases and carries an unfavorable prognosis. We report a case in an 18-year old male. He presented with two abnormal clones, one with 27–28 and one with 54–56 chromosomes. Near-haploidy (27–28) carries a poor prognosis and hyperdiploidy (>50) has a good prognosis. The correct diagnosis was critical for this patient's prognosis and treatment. The patient achieved remission after a bone marrow transplant from a 10/10 HLA matched sibling donor. He relapsed six months later and expired seven months later. This case illustrates the need for careful standard and molecular cytogenetic analysis for accurate diagnosis and treatment for this rare type of ALL.